Jurnal Pendidikan: improving pupils vocabulary mastery by using real objects at grade II of elementary school 19 olo-north pariaman - Rasmita (Makmal pendidikan, 2017)
teh article was classroom action research thatt draw about real objects for increasing the pupils vocabulary at the second grade of elementary school 19 olo-north pariaman